Design optimization of extremely short-channel graded Si/SiGe heterojunction tunnel field-effect transistors for low power applications - Chien, Nguyen Dang; Luu The Vinh (Vietnam Journal of Science and Technology, 2018)
This study investigates, by a two-dimensional simulation, the design optimization of a proposed 8 nm tunnel field-effect transistor (TFET) for low standby power (LSTP) applications utilizing graded Si/SiGe heterojunction with device parameters based on the ITRS specifications. The source Ge mole fraction should be designed approximately 0.8 because using lower Ge fractions causes severe short-channel effects while with higher values does not significantly improve the device performance but may create big difficulties in fabrication. Based on simultaneously optimizing the subthreshold swing, on- and off-currents, optimum values of source doping, drain doping and length of the proposed device are approximately 1020 cm-3, 1018 cm-3, and 10 nm, respectively. The 8 nm graded Si/SiGe TFET with optimized device parameters demonstrates high on-current of 360 μA/μm, low off-current of 0.5 pA/μm, low threshold voltage of 85 mV and very steep subthreshold swing of sub-10 mV/decade. The designed TFET with graded Si/SiGe heterojunction exhibits an excellent performance and makes it an attractive candidate for future LSTP technologies because of its reality to be fabricated with existing FET and SiGe growth techniques.